1997
DOI: 10.1046/j.1365-3059.1997.d01-224.x
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen‐induced changes in colony density and spore production of Erysiphe graminis f.sp. hordei on seedlings of six spring barley cultivars

Abstract: The influence of increasing nitrogen supply (30, 60, 120 and 240 mg N per pot) on susceptibility was studied on seedlings of six cultivars of spring barley inoculated with virulent isolates of powdery mildew. The colony density (CD) measured as colonies per cm 2 was significantly increased with increasing application of nitrogen on all cultivars, and a significant interaction was found between N and cultivar. The different reactions of the cultivars could not be ascribed to lack of N uptake. In general, incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
48
0
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 24 publications
4
48
0
3
Order By: Relevance
“…There is a wealth of epidemiological data showing that the severity of fungal pathogens is increased by nitrogen fertiliser input to the host plant. This applies in particular to biotrophic pathogens and hemibiotrophic pathogens such as Puccinia spp., Blumeria graminis, Magnaporthe grisea and Phytophthora infestans (Last 1962;Matsuyama and Diamond 1973;Huber and Watson 1974;Hofmeester 1992;Jensen and Munk 1997;Newton and Guy 1998). The techniques developed in this study would make the C. fulvum±tomato interaction an ideal system in which to directly monitor the eect of nitrogen fertilisation on pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of epidemiological data showing that the severity of fungal pathogens is increased by nitrogen fertiliser input to the host plant. This applies in particular to biotrophic pathogens and hemibiotrophic pathogens such as Puccinia spp., Blumeria graminis, Magnaporthe grisea and Phytophthora infestans (Last 1962;Matsuyama and Diamond 1973;Huber and Watson 1974;Hofmeester 1992;Jensen and Munk 1997;Newton and Guy 1998). The techniques developed in this study would make the C. fulvum±tomato interaction an ideal system in which to directly monitor the eect of nitrogen fertilisation on pathogenicity.…”
Section: Discussionmentioning
confidence: 99%
“…Increased supply of N to the plant led to higher spore production by the powdery mildew fungus Oidium lycopersicum, and increased leaf colonization by the bacterium Pseudomonas syringae pv tomato suggested that increased leaf N caused greater susceptibility to these pathogens. N fertilization has been shown to increase levels of powdery mildew attack on cereals in the field, and experiments carried out on seedlings of six different barley cultivars showed a positive correlation between N application and powdery mildew disease severity (Jensen and Munk, 1997). A further link between host and pathogen N was noted by Robert et al (2002) who correlated spore production by the rust fungus Puccinia triticina in wheat seedlings.…”
Section: Nitrogen Fertilization and Pathogenicitymentioning
confidence: 94%
“…Nitrogen addition has been hypothesized to increase foliar fungal disease severity by mechanisms such as increasing the concentration of foliar N available as a resource to the pathogens (the nitrogendisease hypothesis) (Jensen and Munk 1997;Nordin et al 1998;Strengbom et al 2002), decreased production of defensive compounds (Sander and Heitefuss 1998), or increased microclimate humidity (Jenkyn 1976) (cited by Mitchell et al 2003). In the present study, in both the pot and field experiments, wheat foliar N concentrations increased significantly with increasing N rate and the DI and DSI of wheat were highly and positively correlated with the foliar N concentrations in accordance with the nitrogen-disease hypothesis (Jensen and Munk 1997;Nordin et al 1998;Strengbom et al 2002), implying that N fertilizer management may be a key component in the control of wheat powdery mildew.…”
Section: Influence Of N Addition On Wheat Powdery Mildewmentioning
confidence: 99%